Karakteristik Ekstrak Pewarna Alami Bunga Bugenvil (Bougainvillea glabra) Pada Perlakuan pH Pelarut Dan Ukuran Partikel Menggunakan Metode Microwave Assisted Extraction - Ardita, Mia; Wartini, Ni Made; Hartiati, Amna (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2026)
Bougainvillea flower (Bougainvillea glabra) has potential as a source of natural colorant due to the presence of betacyanin pigment and bioactive compounds such as antioxidants. The extraction of these compounds can be carried out using the Microwave Assisted Extraction (MAE) method. This study aims to investigate the effect of solvent pH and particle size on the characteristics of natural colorant extract from bougainvillea flower, including extract yield, total betacyanin content, color intensity (a*, b*), and antioxidant capacity, as well as to determine the optimal solvent pH and particle size to obtain the best quality extract using the MAE method. The study was conducted using a factorial Completely Randomized Design (CRD) with two factors: solvent pH variations (1, 1,62, and 2,25) and particle sizes (40, 60, and 80 mesh). The results showed that both solvent pH and particle size significantly affected yield, total betacyanin content, redness level (a*), and yellowness level (b*). The interaction between the two factors had a significant effect on yield, total betacyanin content, redness (a*), and antioxidant capacity, but had no significant effect on yellowness (b*). The best treatment based on the effectiveness index test was obtained at solvent pH 2.25 with a particle size of 80 mesh, resulting in an extract with the following characteristics: yield of 81,89 ± 0,40%, total betacyanin content of 22,84 ± 1,20 mg/100g, redness level (a*) of 30,84 ± 0,55, yellowness level (b*) of 17,15 ± 0,61, and antioxidant capacity of 320,97 ± 6,08 mg GAEAC/g.